Hubungan Tingkat Pengetahuan Masyarakat Dan Persepsi Masyarakat Dengan Vaksinasi Covid-19 Di Lembang Rano Utara Kecamatan Rano Kabupaten Tana Toraja - Hayuti Windha Pagiu; Elche Tandiallo (Jurnal Rumpun Ilmu Kesehatan, 2023)
The Covid-19 vaccine is a breakthrough to fight and treat Covid-19. The family in a situation like this is the first and main defense system for the country in preventing the spread of Covid-19 transmission. It is the role inherent in the family that needs to be optimized as a preventive strategy in dealing with Covid-19 through the Covid-19 vaccine. This research aims to determine the relationship between the level of knowledge and perception of the community with Covid-19 vaccination in North Lembang Rano, Rano District, Tana Toraja Regency in 2022. This research method is observational with a cross-sectional approach, the sample size is 92 respondents who are representative of the population. The sampling technique in this research is purposive sampling technique. Data was collected using a questionnaire and tested statistically with the help of the SPSS computer program, and presented in the form of tables and narratives. From the results of this research, it was found that the majority of respondents were female, namely 57 people (62.0%), the majority of respondents aged 31-50 were 49 people (53.3%), the majority of respondents worked as farmers, namely 35 people (38%) The majority respondents with good knowledge were 84 people (91.3%), the majority of respondents with good perception were 90 people (97.8%) and the majority of respondents with good Covid-19 vaccination were 49 people (53.3%). The results of the Fisher's Exact Test statistical test showed that there was a relationship between the level of knowledge and Covid-19 vaccination with a p-value = 0.006 and it was also found that there was a relationship between public perception and Covid-19 vaccination with a p-value = 0.007. Based on the results of this research, it can be concluded that there is a relationship between the level of knowledge and perception of the community with Covid-19 vaccination in North Lembang Rano, Rano District, Tana Toraja Regency in 2022. It is recommended for the public to increase Covid-19 vaccination and always maintain their health by having regular check-ups and Always adopt a healthy lifestyle to avoid health problems.